FACTORS THAT INFLUENCE ANXIETY IN MOTHERS IN LABOR IN THE FACING SECTION CESAREAN (SC) DELIVERY - Dyah Siwi Hety; Zulfa Rufaida (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Background: Anxiety occurs due to factors or sources that are considered a threat or endanger the individual. Facing a section cesarean (SC) operation can cause anxiety in the mother; excessive anxiety can affect the smoothness of the birth operation planObjective: to analyze the relationship between maternal characteristic SC and the mother's anxiety level in facing SC delivery at Wates Husada Hospital.Methods: correlation analytical research, with a cross-sectional design. The sampling technique used was purposive sampling for 1 month, which obtained up to 33 samples. This research was carried out at Wates Husada Hospital in January 2024. The independent variable was maternal characteristic, and the dependent variable was anxiety in facing SC. Data were collected using the APAIS anxiety questionnaire. Statistical test using the Kendal Tau test.Results: There is a relationship between age, parity, cause of SC, and anxiety about facing cesarean section (SC) delivery at Wates Husada Hospital. Health workers, especially midwives, provide appropriate midwifery care to reduce anxiety in patients who will undergo caesarean section surgery. Based on the results of the reliable statistical test, the p values obtained for the variables age, parity, causes of (SC), and anxiety are 0.010, 0.023, and 0.023.Conclusion: The level of maternal anxiety regarding Caesarean delivery (SC) is related to age, parity, and cause of SC.